Thermoexpansive polymeric materials - Kostrzewa, M.; Molenda, J.; Prot, T. (Polimery, 2022)
A review covering methods for preparing microcapsules, including Author’s own works on preparation of microcapsules that expand on heating. Scanning electron microscopy (SEM) and IR spectroscopy were used to characterize the product of microencapsulation of n-hexane on radical emulsion terpolymerization of acrylonitrile, methyl mathacrylate and vinylidene chloride, initiated with lauroyl peroxide and additionally with azobisisobutyronitrile which was used as a solid porophor.